(._.)/ dont 4get 2 txt me plz! Linguistic and discoursal features of short message service by female texters - Yusuf, Yunisrina Qismullah; Natsir, Yuliana; Yusra, Siti Rahimah (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
The practicality and limited space of SMS have become features encouraging the emergence of various forms of SMS language. An analysis of SMS from 20 Acehnese female students in the University of Syiah Kuala was therefore carried out to inspect the elements of language employed within the text messages. The data of 110 SMS gathered through a mobile device were thoroughly analyzed and later categorized into linguistics and discoursal features. The result showed that female students tend to write about their psychological conditions in SMS by employing logogram and pictogram. A number of findings on omitted letters and nonstandard spelling were also indicated in their SMS. They rarely used initialism and shortening in writing the text messages because it is believed that these features can diminish intelligibility. These females also wrote complex messages and employed various languages into their text messages, including the national language (Indonesian), the language of their religion (Arabic), the language from media influence (Japanese), and their mother tongue (Acehnese). Their circumstance of being multilingual has expanded their linguistic performance in employing, typing, and inventing lively SMS. It is also interesting to discover that these texters created new symbols that are not generally found in SMS to identify their reciprocal relationship of the same culture and belief.